In-situ study of acoustomigration by scanning acoustic force microscopy - Hesjedal, T; Kubat, F; Mohanty, J; Ruile, W; Reindl, L (2003)
High-power operation of surface acoustic wave devices may lead to stress induced material transport, so-called acoustomigration. We used Scanning Acoustic Force Microscopy (SAFM) to study acoustomigration of metal structures in-situ, i.e. during the high-power loading of the device. SAFM allows for the simultaneous measurement of the acoustic wavefield and the topography with submicron lateral resolution. We present acoustic wavefield and topographic image sequences giving a clear insight into the nature of the film damage on a submicron scale. The 900 MHz test structures were fabricated on 36°YX-LiTaO3 incorporating 420 nm thick Al electrodes. By correlating the acoustic wavefield mapping and the local changes in the topography point-by-point, already the initial changes of the granular structure that lead to acoustomigration can be visualized.